Complete re-utilization of waste concretes: Valorisation pathways and research needs - Villagrán Zaccardi, Yury Andrés (2022)
Global demand for buildings and infrastructure is extremely high as provision of shelter, sanitation and healthcare are paramount to safeguard the world's growing population. Concrete is a preferred construction material to meet this demand, but its production is leading to overexploitation of natural gravel and sand, causing an environmental crisis in regions where these materials are extracted unsustainably. Waste concrete is available globally, particularly in regions with fast growth of the built environment, and those struck by coordinated attacks, earthquakes or severe weather events. Waste concrete has mainly been used for producing recycled aggregates; however, its full recycling is still not practiced. Alternative uses include applications as fine recycled aggregates, supplementary cementitious materials, filler, and feedstocks for clinker production. These technologies still face challenges concerning their adoption and eco-efficiency. Restricted knowledge and operational barriers have also prevented implementation of beneficiation technologies for complete re-recycling of waste concretes, particularly the fine fractions produced during crushing. Despite these issues, it is recognised that the complete utilization of waste concrete offers unique opportunities for supply chain security, reducing natural resources consumption and enabling to move towards a Circular Economy. Harmonizing current practices for the treatment of waste concrete and the by-products generated during their processing, is a first step toward policy and standards development to enable their widespread use. This critical discussion addresses challenges and opportunities, as well as facilitation strategies needed to progress the complete re-utilization of waste concrete as a valuable resource for creating sustainable future infrastructure.